Modeling, full identification and control of the mitsubishi PA-10 robot arm - Bompos, N.A.; Artemiadis, P.K.; Oikonomopoulos, A.S.; Kyriakopoulos, K.J. (2007 IEEE/ASME international conference on advanced intelligent mechatronics, 2007)
This paper presents the modeling, identification and control of the 7 degrees of freedom (DoFs) Mitsubishi PA-10 robot arm. The backdrivability, high accuracy positioning capabilities and zero backlash afforded by its harmonic drive transmission, make the PA-10 ideal for precise manipulation tasks. However, the lack of any technical knowledge on the dynamic parameters of its links and the non linear characteristics of friction at its joints, make the development of an accurate dynamic model of the robot extremely challenging. The innovation of this research focuses on the development of the full dynamic model of the PA-10 robot arm, the development of a new non linear model for the friction at its joints, the estimation of the stiffness characteristics of its joints and finally the full identification of the dynamic parameters of the robot arm. The accuracy of the full dynamic model identified is proved by an end-effector trajectory tracking task using a model-based inverse dynamic controller.